Effects of long-term application of mineral and organic fertilizers on dynamics of nitrogen pools in the sandy soil of the Sahel region, Niger - Suzuki, K.; Matsunaga, R.; Hayashi, K.; Matsumoto, N.; Tobita, S.; Bationo, B. André; Okada, Kensuke (Elsevier, 2017)
Our study on soil N dynamics was conducted in the rainy season of 2005 and 2006. It focused on the effects of soil managements with sole and combined applications of mineral and organic fertilizers in the long-term experiment conducted since 1993 in the Niamey Center of the International Crop Research Institute for the Semi-Arid Tropics, Niger. Treatments were established with each three input levels of chemical fertilizer as urea and SSP, pearl millet residue, and cattle manure. The lowest and highest levels were focused in our study. Treatments with 2700 kg ha−1 of applied crop residue showed high total N in the soil surface (< 30 cm), but did not show any change in the deeper layer (> 30 cm) or seasonal changes. Phosphate-buffer extractable organic nitrogen (PEON) as an indicator to estimate available N in the soil was not affected by the different treatments; however, similar seasonal changes were identified in all treatments. PEON in soil surface was high right before the rainy season began, then gradually decreased with increasing rainfall and remained at approx. 10 mg kg−1 until the end of the season. In deeper layer, leaching was identified after heavy rainfall but at least 5 mg kg−1 of PEON remained during the season. Inorganic N (NO3single bondN plus NH4single bondN) increased in the soil surface right after fertilizer application but its effect disappeared in a few weeks. The ‘Birch effect’ affected the fluctuations of PEON and inorganic N at the start of rains in the Sahel region of Niger.